Asbestos in the Construction Industry: A Critical Analysis of Impacts on Health and the Environment - Darwis Baso; Miftahul Khaer (Universitas Tribhuwana Tunggadewi Malang, 2026)
Asbestos exposure in the construction sector necessitates mitigation due to its severe health and environmental impacts. This study aims to analyze the effects of asbestos exposure and evaluate effective mitigation and risk management strategies. A Systematic Literature Review (SLR) method was applied to examine empirical studies and policies related to asbestos exposure in construction activities. The findings show that respirable asbestos fibers are the primary cause of chronic lung diseases such as asbestosis, lung cancer, and mesothelioma, which have long latency periods. Workers involved in demolition, cutting, insulation installation, and renovation are at the highest risk, while secondary exposure through contaminated work clothing extends risks to families and surrounding communities. Asbestos waste is persistent, easily dispersed, and capable of contaminating air, soil, and water. Effective mitigation strategies include strict regulations, control technologies, administrative procedures, and worker education, with thermal vitrification identified as a promising waste treatment option. This study recommends longitudinal health research, real-time fiber monitoring technologies, mitigation innovation, and waste management models.